Defarmation Against Government in National Criminal Code: Review on Freedom of Expression and Opinion Rights - Kurdi Kurdi; Sandi Yudha Prayoga; Teuku Ahmad Dadek (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2026)
The offense of insulting the government or state institutions is considered contrary to the right to freedom of expression and opinion. This study aims to determine the regulation of the offense of insulting the government or state institutions based on the perspective of the right to freedom of expression and opinion. In addition, it also aims to compare the regulation of insulting offenses against the government or state institutions in Indonesia with other countries. The research is included in normative legal research using a statutory approach, conceptual approach, and comparative legal approach. The results show that the offence under discussion does not violate the right to freedom of expression and opinion because Article 240 of the National Criminal Code has clearly distinguished between the act of